Evaluation of HY-8 Modeling Tool for Hydraulic Analysis of Selected Culverts along Ilorin -Jebba Road, Kwara State, Nigeria. - Adeogun, A. G.; Akinpelu, M. A.; Yusuf, M. A.; Animashaun, R. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
In this study, selected culverts along Ilorin – Jebba road, Kwara State were hydraulically analyzed using HY-8 modelling tool. Hydrological analyses of the culverts were performed using rational method for the computation of design discharges. On site information such as tail water data such as channel type and bottom width, roadway data such as crest length and culvert data such as culvert material and span were collected from each of the culverts and were used in conjunction with estimated design discharge as input data for HY-8 modeling tool to facilitate the hydraulic analysis of the culverts. Hydrological analysis showed that the highest design flow of 9.09 m3/s was obtained at culvert located at Km 11+775 while the least design flow of 1.83 m3/s was obtained at culvert located at Km 3+300. Hydraulic analysis revealed that seven of the analyzed culverts have adequate capacity to convey the design flow while three culverts were found inadequate to convey the design flow and therefore, need to be resized. The outcome of this study will arouse the interest of engineers in the usage of the tool in sizing hydraulic culverts most especially in Nigeria and other Saharan African countries.